Pesantren Lansia Sebagai Wadah Pembinaan Husnul Khatimah - Imas Kania Rahman; Novi Maulana Yusup; Didin Hafidhuddin (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2021)
Abstract: This research was motivated by a lack of understanding of Muslims, especially the elderly, regarding husnul khatimah. Husnul khatimah is a good condition at the end of human life which must be the ideal of every Muslim to achieve it. To reach husnul khatimah requires understanding and training. The presence of an elderly Islamic boarding school (Pesantren lansia) brings closer understanding and training for the elderly to try to reach husnul khatimah. This article aims to analyze and provide an overview of how the elderly Islamic boarding school has become a forum for the formation of husnul khatimah and the activities contained in it. In this research, the method used is descriptive method with a qualitative approach. The data collection technique that used by researchers is use interview techniques, observation and document study. The results showed that the elderly Islamic boarding school is a very suitable and important place for the guidance of husnul khatimah. In this case, Peantren Lansia Lembaga Dakwah dan Sosial Qobasat Annur Foundation, provides a training program for the elderly to strengthen and care for their aqidah and religious deeds in order to achieve husnul khatimah Abstrak: Penelitian ini dilatar belakangi oleh kurangnya pemahaman kaum muslimin khususnya usia lanjut mengenai husnul khatimah. Husnul khatimah merupakan kondisi baik pada akhir kehidupan manusia yang harus menjadi cita-cita setiap muslim untuk meraihnya. Untuk meraih husnul khatimah perlu pemahaman dan juga latihan. Hadirnya pesantren lansia mendekatkan pemahaman dan latihan bagi para lansia untuk berusaha menggapai husnul khatimah. Artikel ini bertujuan untuk menganalisis dan memberikan gambaran bagaimana pesantren lansia menjadi wadah pembinaan husnul khatimah beserta kegiatan-kegiatan yang terdapat di dalamnya. Dalam penelitian ini metode yang digunakan adalah metode deskriptif dengan pendekatan kualitatif. Adapun teknik pengumpulan data yang dilakukan oleh peneliti adalah dengan menggunakan teknik wawancara, observasi dan studi dokumen. Hasil penelitian menunujukkan bahwa pesantren lansia merupakan wadah yang sangat cocok dan penting untuk pembinaan husnul khatimah. Dalam hal ini Pesantren Lansia Lembaga Dakwah dan Sosial Qobasat Annur Foundation menghadirkan program pembinaan kepada para lansia untuk menguatkan dan merawat aqidah dan amal ibadahnya guna mencapai husnul khatimah.